THE ESSENCE OF THE STATE CONTROL (SUPERVISION) AND THE GENESIS OF ITS LEGISL ATIVE DEFINITION - M. A. Lapina (Финансы: теория и практика, 2017)
The article considers theoretical issues related to government control (supervision) within public administration system, as well as trends in the development of legislation related to the concept of government control. The article analyzes the terms “government control”, “administrative supervision” and “state control (supervision)” in the context of public administration theory and administrative law. The article describes the purpose and stages of control and supervisory activities of government bodies based on the case study in the economic relations sphere. The author substantiates legislative recognition of the concept of “state control (supervision)” in the modern Russian supervisory legislation. The methodological basis of the article uses the latest achievements in the cognitive theory. The study employed general philosophical methods, theoretical methods (dialectics, comparative method, systematic analysis, synthesis, analogy, deduction, observation, and modeling), traditional legal methods (formal logic), as well as the method of expert estimates, etc. The main conclusion drawn from the results of study is the confirmation of legislative recognition of the concept of “state control (supervision)” which combines the external government control with elements of administrative supervision, particularly when concerning administrative coercive measures. The novelty of the paper is in introducing the model based on concepts, objectives and functions of government control (supervision) in view to further develop control and supervisory legislation within the system of public administration.